Transforming residential interventions practical strategies and future directions - Caldwell, Beth; Lieberman, Robert E.; LeBel, Janice; Blau, Gary M. (Routledge, 2020)
Transforming Residential Interventions: Practical Strategiesand Future Directionscaptures the emerging changes, exciting innovations, and creative policies and practices informing ground-breaking residential programs. Building on the successful 2014 publication Residential Interventions for Children, Adolescents, and Families, this follow-up volume provides a contemporary framework to address the needs of young people and their families, alongside practical strategies that can be implemented at the program, community, system, and policy levels. Using the Building Bridges Initiative as a foundation, the book serves as a "how-to manual" for making bold changes to residential interventions. The reader will learn from a range of inspired leaders who, rather than riding the wave of change, jumped in and created the wave by truly listening to and partnering with their youth, families, advocates, and staff. Chapters provide real-time practice examples and specific strategies that are transformational and consider critical areas, such as family and youth voice, choice and roles, partnerships, permanency and equity, diversity, and inclusion. These methods benefit youth with behavioral and/or emotional challenges and their families and will improve an organization's long-term outcomes and fiscal bottom line. This book is for oversight agencies, managed care companies, providers of service, advocates, and youth/family leaders looking for an exemplar guide to the new frontier of residential intervention. In this era of accountability and measurement, it will become a trusted companion in leading residential interventions to improved practices and outcomes
Description based on online resource; title from digital title page (viewed on February 20, 2020)
Keywords: Child psychotherapy / Residential treatment; Adolescent psychotherapy / Residential treatment